SOME PRELIMINARL Y RESULTS OF APPLIED ECOHAM MODEL FOR NUTRIENT DYNAMICS IN VAN PHONG BAY, KHANH HOA, VIETNAM - Chien, Thai Ngoc; An, Nguyen Tac; Long, Bui Hong (Vietnam Journal of Marine Science and Technology, 2006)
SOME PRELIMINARL Y RESULTS OF APPLIED ECOHAM MODEL FOR NUTRIENT DYNAMICS IN VAN PHONG BAY, KHANH HOA, VIETNAM